2013
DOI: 10.1021/tx400204d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Glutathione S-Transferases on Glutathione-Dependent Inactivation of Cytochrome P450-Dependent Reactive Intermediates of Diclofenac

Abstract: Idiosyncratic adverse drug reactions due to the anti-inflammatory drug diclofenac have been proposed to be caused by the generation of reactive acyl glucuronides and oxidative metabolites. For the oxidative metabolism of diclofenac by cytochromes P450 at least five different reactive intermediates have been proposed previously based on structural identification of their corresponding GSH-conjugates. In the present study, the ability of four human glutathione S-transferases (hGSTs) to catalyze the GSH-conjugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…DCF quinone imine metabolites have been shown to be reduced by NAD(P)H:quinone oxido-reductase1 and conjugated to GSH by GSTs (Dragovic et al, 2013;Vredenburg et al, 2014). Our data confirming that differentiated HepaRG cells contained higher levels of GST A1/2 and M1/2 than their undifferentiated counterparts and HepG2 cells and showing their higher sensitivity to DCF following GST inhibition by ethacrynic acid, brought further support to their lower sensitivity to apoptotic effects of DCF.…”
Section: Dcf Induced An Apoptotic Response In Both Differentiated Andmentioning
confidence: 99%
“…DCF quinone imine metabolites have been shown to be reduced by NAD(P)H:quinone oxido-reductase1 and conjugated to GSH by GSTs (Dragovic et al, 2013;Vredenburg et al, 2014). Our data confirming that differentiated HepaRG cells contained higher levels of GST A1/2 and M1/2 than their undifferentiated counterparts and HepG2 cells and showing their higher sensitivity to DCF following GST inhibition by ethacrynic acid, brought further support to their lower sensitivity to apoptotic effects of DCF.…”
Section: Dcf Induced An Apoptotic Response In Both Differentiated Andmentioning
confidence: 99%
“…In recent studies with diclofenac and clozapine, GSTs have been shown to increase GSH-conjugation rates, and also completely GST-dependent conjugation reactions have been observed with cytosolic human GSTs [30,31]. Here, the formation of GSH conjugates was very similar in incubations with liver microsomes and S9 fractions, suggesting that cytosolic GSTs did not have a clear role in formation in the reactions.…”
Section: Microsomes S9 S9 With All Cofactors Heparg Human Hepatocytesmentioning
confidence: 65%
“…Here, the formation of GSH conjugates was very similar in incubations with liver microsomes and S9 fractions, suggesting that cytosolic GSTs did not have a clear role in formation in the reactions. This may be due to involvement of microsomal GSTs, or due to a high added GSH-concentration (4 mM), which has been earlier shown to decrease the GSTdependency of conjugate formation [30,31]. It was anticipated that the GSH conjugation reactions would have demonstrated a high rate with hepatocyte experiments, yet possibly with different conjugates than those observed with liver microsomes.…”
Section: Microsomes S9 S9 With All Cofactors Heparg Human Hepatocytesmentioning
confidence: 99%
“…In the case of GST, levels and activity can be quantified via the removal of chlorine from substrate 1-chloro-2,4-dinitrobenzene (CDNB) [138]. While CDNB can be used as a substrate for total GST activity, p -nitrobenzyl chloride (NBC), 1,2-chloro-4-nitrobenzene (DCNB), and trans-4-phenyl-3-buten-2-one (PBO) can be used to detect GSTM activity, and 1,2-epoxy-3-(p-nitrophenoxy)propane (EPNP) and dichloromethane (DCM) can be used as substrates for GSTTs [139, 140]. …”
Section: Assays Detecting Susceptibility For Idiosyncratic Reactionsmentioning
confidence: 99%
“…Surendradoss et al used HPLC and MS to quantify valproyl 1-O-acyl-glucuronide (VPA-G), the phase II metabolized drug of valproic acid [142, 143]. Additionally, diclofenac conjugated to GSH has been measured via HPLC to assay for GST activity [140]. The drawback to using these technologies is that metabolites can only be quantified in relative terms without giving exact values as to the forms of drug present in a solution.…”
Section: Assays Detecting Susceptibility For Idiosyncratic Reactionsmentioning
confidence: 99%